Phenomenology, architecture, and the built world : exercises in philosophical anthropology - Dodd, James, 1968- (Studies in Contemporary Phenomenology, 2017)
Phenomenology, Architecture and the Built World is an introduction to the methods and basic concepts of phenomenological philosophy through an analysis of the phenomenon of the built world. The conception of the built world that emerges is of space and time fashioned in accordance with a living understanding of what it is for human beings to exist in the world. Human building and making is thus no mere supplementary instrument in the pursuit of the ends of life, but a fundamental embodiment of the self-understanding of human beings. Phenomenological description is uniquely capable of bringing into view the physiognomy of this understanding, its texture and complexity, thereby providing an important basis for a critique of what constitutes its essence and its conditions of possibility.